DEVELOPMENT STRATEGIES OF VILLAGE-OWNED ENTERPRISES (BUMDES) TO SUPPORT ECONOMIC RESILIENCE IN TOMBOLO PAO DISTRICT, GOWA: Strategi Pengembangan Badan Usaha Milik Desa (BUMDes) untuk Mendukung Ketahanan Ekonomi di Kecamatan Tombolo Pao, Gowa - Anshar, Muhammad; Siradjuddin, Irsyadi (Unit Penelitian dan Pengabdian Masyarakat Politeknik Pembangunan Pertanian Gowa, 2025)
This study aims to analyze the development classification status of Village-Owned Enterprises (Bumdes) and to develop strategies for Bumdes in supporting regional economic resilience in Tombolo Pao District, Gowa Regency. The assessment of Bumdes development is based on Presidential Regulation No. 11 of 2021 concerning Bumdes, covering variables such as institutional framework, regulations, Bumdes operations, administration, reporting and accountability, capital and assets, and the impact of Bumdes on the community. A SWOT analysis method was employed to formulate Bumdes development strategies. The results of the study indicate that the classification status of Bumdes development in the Tombolo Pao District is as follows: Advanced Bumdes in two villages, namely Pao with a score of 89 and Kanrepia with a score of 88. Developing Bumdes in four villages, namely Balaromang, Tonasa, Mamampang, and Erelembang, with scores of 83, 82, 81, and 77 respectively. Growing Bumdes are found in two villages, Tabbinjai and Balassuka, with scores of 74 each. The strategy for Bumdes to support regional economic resilience in Tombolo Pao is as follows: Advanced Bumdes need to maintain good performance, continue innovating, and expand their business networks. Developing Bumdes should strengthen governance, improve access to capital, and diversify their business ventures. Growing Bumdes need to build a strong foundation, develop human resource capacity, and focus on developing profitable businesses